Molecular characterization and multidisciplinary management of Gerbich hemolytic disease of the newborn. Issue 6 (22nd February 2018) - Levitt, Rebecca N.; Gourri, Elise; Gassner, Christoph; Banez‐Sese, Grace; Salam, Abdus; Denomme, Gregory A.; Yang, Elizabeth
Abstract: Gerbich (Ge) antigens are high frequency red cell antigens expressed on glycophorin C (GYPC) and glycophorin D. Hemolytic disease of the fetus and newborn (HDFN) due to Gerbich antibody is rare and presents a clinical challenge, as Gerbich negative blood is scarce. We report a case of HDFN due to maternal Ge3 negative phenotype and anti‐Ge3 alloimmunization, successfully managed by transfusion of maternal blood. Molecular testing revealed that the mother has homozygous deletion of exon 3 of GYPC, the father is homozygous wildtype for GYPC, and the infant is obligate heterozygote expressing Ge3.